Piracy and Privateers in the Golden Age: Lessons for Today. (3rd July 2018) - Hallwood, Paul; Miceli, Thomas
ABSTRACT: Customary international law has governed high seas piracy for many centuries and is now codified in the United Nations Convention on the Law of the Sea (LOSC). In this article, we discuss the reasons why enforcement against piracy today is less effective than three hundred years ago. We contend that crime, including the crime of piracy, can be modeled as a rational choice that is responsive to expected rewards and punishments. Based on this view, we argue that three hundred years ago, the free rider problem resulting from enforcement on the high seas was less prevalent than it is today because seaborne trade was more concentrated in the vessels of a few countries, making enforcement more like internal than international policing. The persistence of piracy today also stems from a continuing low probability of capture coupled with lenient punishments. In addition to enforcement differences, we contrast the sources of piracy in the two eras—in the earlier period, the end of privateering led many privateers to engage in piracy, whereas today, the main source of pirates in the Western Indian Ocean is the existence of a "failed state, " and off West Africa and South East Asia pirates are common criminals.